The genetics of pain - Pekel, Ali Ferit (Cerrahpaşa Medical Journal, 2013)
Individuals are unique as in their fingerprints. Shared features among people, regarding social and culturel issues constitutes ethnic and national societies while common biological features lead to shared treatment strategies. Details of our shared and differing emotional/physical attitudes rely muchly upon what we inherited genetically. Once identified the sequenced human genom, the reasons of the individual varience of human response to external effects became more clear. In pain management it is reflected as individual variation in both to response to pain and response to anagesics. This is probably produced by the multiple single-nucleotide polymorphisms –SNPs- in genes encoding drug metabolism enzymes, transporters, receptors, ion channels, and neurotransmitter systems. This novel explanation to known subjective pain experience is increasingly questioning the appropriateness of previously established conventional pain management strategies, asking; whether it is possible to produce drugs spesific for the subgroups of any society? Maybe the final question will dare to ask if human will be tailored by means of analgesics ?!..